2016
DOI: 10.1186/s13635-016-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

DB-SECaaS: a cloud-based protection system for document-oriented NoSQL databases

Abstract: The trend of cloud databases is leaning towards Not Only SQL (NoSQL) databases as they provide better support for scalable storage and quick retrieval of exponentially voluminous data. One of the more prominent types of NoSQL databases is document-based storage, which is being increasingly used in the dynamic cloud paradigm. However, there are inherent security issues in cloud, including remote data residency along with the non-existent control of owners over their own data. In addition to that, the inherent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We have identified the NoSQL databases are considered to be inherently insecure, and there is a need for better security standards and encryption protocols to provide secure data storage. Previous research studies have identified certain security measures that could help to mitigate the security attacks and lessen the security concerns in Big Data as mentioned earlier [35]. Our indepth analysis of the currently available NoSQL databases indicates that they offer either none or some security controls depending upon the vendor and license.…”
Section: Proposed Framework For Nosql Database Securitymentioning
confidence: 77%
See 1 more Smart Citation
“…We have identified the NoSQL databases are considered to be inherently insecure, and there is a need for better security standards and encryption protocols to provide secure data storage. Previous research studies have identified certain security measures that could help to mitigate the security attacks and lessen the security concerns in Big Data as mentioned earlier [35]. Our indepth analysis of the currently available NoSQL databases indicates that they offer either none or some security controls depending upon the vendor and license.…”
Section: Proposed Framework For Nosql Database Securitymentioning
confidence: 77%
“…For instance, the use of key distribution encryption mitigates the possibility of data alteration. Further, the use of key distribution with federation identity authorization mitigates attacks such as DoS, privilege abuse and injection [35]. By encrypting sensitive data before transit or with encrypted SSL connection, secure transmission or processing of data (data in transit) can be achieved.…”
Section: Proposed Framework For Nosql Database Securitymentioning
confidence: 99%
“…This finding is consistent with the DIT because cloud computing as an evolving disruptive innovation brings with it many challenges such as data security that needs to be addressed to minimize data breaches. In the review of professional and academic literature, Ghazi et al (2016) proposed that SSL is a strategy to protect encrypted data in transit so that the right person receives the data in the correct form. Singh and Chatterjee (2017) indicated that a middleman attack to the data occurs in transit due to a lack of security configuration of an SSL.…”
Section: Secure Socket Layer (Ssl)mentioning
confidence: 99%
“…In [18], a database security-as-a-service (DB-SECaaS) over a document-oriented database hosted in the cloud was proposed to ensure that access to the data is granted only to authorized users on a need-to-know basis. The system has a service-oriented architecture, which allows deploying different components for performing exact functions as distinct services.…”
Section: Related Workmentioning
confidence: 99%